(untitled) (Sains Humanika, 2020)
This study aims to survey the level of readiness of Islamic education teachers toward multimedia platform in teaching, also the difference of the level of readiness based on the demography of GPI. The study involved 127 Islamic education teachers who taught subjects under Islamic education such as Quranic and as-Sunnah Education, Shariah Islamic Education and Tasawwur Islamiah in Kelantan Islamic Foundation secondary school. The quantitative data of the questionnaires instrument were analysed descriptively using the Statistical Package for the Social Sciences (SPSS) version 25 to obtain the frequency, percentage, mean, interpretation and standard deviation while inference analysis using t-Test, one-way ANOVA test and Post hoc Scheffe test. The findings from the level of readiness such as level of knowledge, level of skill and level of attitude showed a high level of moderation (min=3.70, sp=0.62). The inferential analysis also showed that there was a significant difference (p<0.05) between the GPI demographics including teaching experience, laptop usage intensity, academic qualifications and diploma in teaching. However, gender, location of teaching, level of teaching and specialization of teaching subjects do not shows significant differences. The study conluded that the level of readiness toward multimedia platform in teaching well but there are differences in the level of readiness based on GPI demographics.